Non dalla testa di Zeus. Heisenberg, Wheeler e il rapporto con il passato della scienza - Furlan, Stefano (Bollettino Filosofico, 2023)
Werner Heisenberg and John Wheeler, besides being crucial figures of 20th-century physics, developed grand views and offered a series of broader reflections whose philosophical interest seems beyond doubt. And yet, the genesis of such ideas and their intertwinement with other philosophical viewpoints get systematically distorted, impaired, decontextualized and/or neglected. This contribution aims to offer a few methodological considerations to address more fruitfully, faithfully and interestingly their thought (or that of similar cases), as well as to underline their peculiar (at least for recent physicists) relationship with the past – not irrelevant for who intends to meditate on “Nature and Technology”. Keywords: 20th-Century Physics, Historical Epistemology, Future of Science, Scientific Narratives, Physics-Philosophy Interactions